Implementasi Program Makan Bergizi Gratis pada Tingkat Sekolah Dasar di Kecamatan Padang Utara (Studi Kasus Sekolah Dasar Negeri 18 Air Tawar Selatan) - Melisa Diah; Zikri Alhadi (Lembaga Yasin AlSys, 2026)
The Free Nutritious Meals Program (MBG) is a national priority policy mandated through Presidential Regulation Number 115 of 2025 to break the cycle of malnutrition among elementary school-aged children. Although supported by a substantial national budget and clearly defined targets, the success of the program is largely determined by how the policy is translated at the local implementation level. This study aimed to analyze the implementation of the MBG Program at SDN 18 Air Tawar Selatan, Padang Utara Subdistrict, Padang City, using Merilee S. Grindle’s Policy Implementation Model as the main theory and Michael Lipsky’s Street-Level Bureaucracy theory as a micro-level analytical lens. The study employed a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving 17 informants representing the government, school, food provider, parents, and students. The results revealed a significant gap between the normative policy design and operational realities. In the content of policy dimension, the problems included a mismatch between the menu and local preferences that systematically generated food waste, centralized decision-making, and limited implementation capacity. In the context of implementation dimension, power asymmetries among actors and vertically centralized institutional characteristics were identified. These problems were rooted in the failure of the feedback mechanism, or a broken feedback loop, whereby the field-level knowledge held by street-level bureaucrats was unable to drive improvements in policy design at the central level. This study concludes that the effective implementation of the MBG Program requires strengthened implementation capacity, improved logistics infrastructure, and limited decentralization in adapting menus to local conditions. These findings contribute to the development of public policy implementation studies by emphasizing the importance of feedback mechanisms and the involvement of street-level actors in improving nationwide programs.